2013
DOI: 10.1111/clr.12219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of relationship between preoperative bone density values derived from cone beam computed tomography and implant stability parameters: a clinical study

Abstract: Bone density assessment using CBCT is an efficient method and significantly correlated with implant stability parameters and Lekholm and Zarb index. Thus, it is possible to predict initial implant stability and possibility of immediate or early loading using CBCT scans prior to implant placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
3
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 15 publications
2
61
3
6
Order By: Relevance
“…Previous studies also found significant correlations between Hounsfield unit (HU) values derived from helical CT and implant stability parameters 5,6,23 as well as between density values derived from CBCT and implant stability parameters. 10,11,13 The aforementioned previous studies evaluated the correlations among the techniques giving predictable information about implant stability before implant surgery (ie, density value derived from CT or CBCT) and during implant surgery (ie, subjective bone quality classification, ITV, and RFA). However; relationship and consistency between stability changes of immediately loaded implants and CBCT-derived preoperative bone density assessments have not been evaluated in the literature, yet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies also found significant correlations between Hounsfield unit (HU) values derived from helical CT and implant stability parameters 5,6,23 as well as between density values derived from CBCT and implant stability parameters. 10,11,13 The aforementioned previous studies evaluated the correlations among the techniques giving predictable information about implant stability before implant surgery (ie, density value derived from CT or CBCT) and during implant surgery (ie, subjective bone quality classification, ITV, and RFA). However; relationship and consistency between stability changes of immediately loaded implants and CBCT-derived preoperative bone density assessments have not been evaluated in the literature, yet.…”
Section: Discussionmentioning
confidence: 99%
“…Details of radiological evaluation have been previously described. 13 Cone-beam CT scanning of the maxilla or mandible was performed after positioning either a previously fabricated surgical acrylic template including 1-mm-diameter indicator metal rods located in the center of each missing tooth or the existing removable complete dentures attached to the same indicator rods under the following conditions: 120 kV, 5 mA, a voxel size of 0.2 mm, scan volume 8.5 cm in diameter, and 8.5 cm in height. The proper implant for each previously designated implant area was selected using cross-sectional images.…”
Section: Cbct Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, CBCT has been proposed as a diagnostic method for the determination of bone mineral density [10,11,18,[34][35][36] . Gray values obtained with CBCT are used in an analog way as the HU values for the determination of mineral density [16] and show a linear relationship with the attenuation coefficients of the materials [13,15] , HU values obtained with medical CT [11,12,37,38] , and density values from DEXA [14] .…”
Section: Cone Beam Ctmentioning
confidence: 99%
“…Comparable differences have been reported elsewhere The strong correlation between bone density and regions within the mouth was similar to previous studies (Norton and Gamble, 2001;Turkyılmaz et al, 2007). Salimov et al (2013), evaluated the relationship between preoperative bone density values derived from cone beam CT and implant stability of 65 implants in 17 patients. They found significant correlations among density value derived from cone beam CT, insertion torque, and ISQ values in all clinical variables and reported that cone beam CT was an efficient method for bone density assessment.…”
Section: Discussionmentioning
confidence: 99%